Não é não, não? Um estudo sobre o marcador negativo “não” em discursos políticos de presidentes brasileiros na perspectiva da linguística sistêmico-funcional - Correa, Erick Kader Callegaro (2019)
This thesis aims to explore the lexicogrammar, semantic, evaluative and discoursive potential of the mood Adjunct “no” in political speeches using Systemic Functional Linguistics. To do such, it was necessary: (i) the creation and organization of a representative corpus, comprised of authentic texts of similar context and typology; (ii) the selection of linguistic and discourse theories as well as History approaches in order to describe the political speeches and to the understanding of their conditions of production; (iii) the production of a lexicogrammatical analysis and a semantic discourse analysis to account for the grammatical, linguistic and discursive behavior of the negative Adjunct. That being said, this thesis uses Systemic Functional Linguistics and its descriptive apparatus, the Systemic Functional Grammar, proposed by Halliday and Matthiessen (2004, 2014) as a theoretical base upon the constitution and functioning of language in a lexicogrammar; Appraisal, by Martin and White (2005) was used to account for negation in a semantic level. As support studies on syntactic and semantic traces of the negative mood Adjunct, it was used Tottie (1987), Givón (1993, 2001) and Gouveia (2010). Upon the contextual and discursive understanding of the political speeches, it was used the Discourse-Historical Approach, proposed by Wodak (2001, 2008, 2009, 2012) and Reisigl and Wodak (2001) and as a narrative base for the historical periods from which the texts were produced, it was used Linz and Stepan (1996), Reis (2000) and Barreto e Borges (2016). As to the creation, organization and statistical and textual analysis, it was used Sketch Engine, by Kilgarriff et al (2014), along with Corpus Linguistics, as developed by Berber-Sardinha (2000), and Sinclair (1991) regarding the concepts of collocation and colligation. Using a quali-quantitative research, one hundred (100) political speeches were analyzed, composed of two blocks: fifty (50) speeches from former military presidents (from 1964 to 1985) and fifty (50) speeches from former democrat presidents (from 1985 to 2010). Selecting the five first speeches from their first mandate and the last five speeches from their last mandate, deeming comparative study, this analysis is divided into two levels: a lexicogrammar one and a semantic one. In relation to the first analysis, results show that in speeches from former military presidents, the mood Adjunct “no” is significantly less used in comparison to the speeches of former democrat presidents. Furthermore, the pattern of use of the negative Adjunct is marked by the usage of voiceless clauses and by obligational modulation. Whereas in the speeches from democrat presidents, “no” is highly associated with first personal pronouns, either singular or plural, as well as being collocated with a diverse of processes in comparison to the speeches produced during the military regime. Results show that the inferior frequency of the word “no” in former military presidents’ speeches is due to its dialogical nature: bearing in mind the cultural and institutional configuration of the military regime, marked by Institutional Acts and national control departments, there was no possibility in recognizing a dialogical space between text producer and their audience.